Identification of lipid metabolism-related genes in dapagliflozin treated rats with diabetic cardiomyopathy by bioinformatics - Huang, Xun; Wang, Yunhong; Wan, Rong; You, Zhigang; Huang, Lin (Frontiers in Endocrinology, 2025)
BackgroundDiabetic cardiomyopathy (DCM) is a heart disease caused by the metabolic disorders of glucose and lipids associated with diabetes, leading to heart failure and death in diabetic patients. Dapagliflozin (DAPA) serves as a treatment for managing blood glucose levels in individuals with type 2 diabetes mellitus (DM). However, the specific mechanisms by which DAPA treats DCM are not yet fully understood.MethodsSprague-Dawley (SD) rats (n = 5/group) were randomly divided into control, model, and intervention groups. Lipid metabolism-related genes (LMRGs) were gotten from publicly available database. Differential expression analysis of model vs. control and intervention vs. model samples was performed to obtain differentially expressed genes (DEGs), and the result was recorded as DEGs-Model and DEGs-Intervention. The intersection of genes with opposing expression trends between DEGs-Model and DEGs-Intervention were considered as candidate genes. Subsequently, candidate genes and LMRGs were intersected to acquire hub genes, and the expression of hub genes was analyzed in each group of samples. Then, the mechanism of action of these hub genes were investigated through functional enrichment analysis, gene set enrichment analysis (GSEA), and predictive of m6A binding sites.ResultsUltimately, 68 candidate genes and 590 LMRGs were intersected to derive 2 hub genes (Acsbg1 and Etnppl). Acsbg1 was significantly increase in model group compared with control group. RT-qPCR results confirmed Acsbg1 was obviously higher expression in model group, while Etnppl was significantly lower expression in model group compare to control groups and intervention group. While the expression of Etnppl was significantly increase in intervention group compared with model group. Functional enrichment analyses indicated that Acsbg1 and Etnppl were associated with fatty acid metabolism. The findings of GSEA indicated that Acsbg1 and Etnppl might affect the occurrence and progression of DCM through lysosome. And the Acsbg1 and Etnppl were located at UCAGG in the RNA secondary structure.ConclusionThis study identified 2 hub genes (Acsbg1 and Etnppl) as potential new focal points for diagnosing and treating DCM.